(untitled) (Journal of Informatics Education and Research, 2026)
The purpose of this study was to understand the relation between Triguna Traits and Psychological Well-Being of Adults. Sample included 100 adults residing in India in between the age range of 25-60 years; sample was divided into males (50) and females (50). Data was collected from Vadodara, Ahmedabad and Surat districts of Gujarat state. Scales used for measuring the Triguna Traits & Psychological Well-Being were Triguna scale constructed and standardized by Dr. Gitanjali Roy and Ryff’s Psychological Well-Being scale respectively. Data was analyzed using ‘t’ test and correlation. Results of the study indicated that on Triguna Traits males have shown higher emotional stability as compare to females. On the variables of Psychological Well-Being; males demonstrated higher levels of Self-Acceptance, Environmental Mastery, Autonomy and overall Psychological Well-Being. Moderately negative correlation was found between Tamasic Knowledge and Psychological-Well Being. Low negative correlation was found between Tamasic Knowledge with Environmental Mastery, Personal Growth, Purpose in Life, and Self-Acceptance. Rajasic Habit has low negative correlation with Personal Growth, Purpose in Life, Self-Acceptance, and Psychological Well-Being. Tamasic Habit had a low negative correlation with Environmental Mastery, Personal Growth, Positive Relations, Purpose in Life and Self-Acceptance.